EFL TEACHERS’ APPROVAL AND DISAPPROVAL BEHAVIOR IN CLASSROOM INTERACTION - Nurul Fachrunnisa (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2019)
The objectives of the research were to find out: (1) the kinds of approval and disapproval behavior used by EFL teachers in classroom interaction, (2) the most frequently used of approval and disapproval behavior by EFL teachers in classroom interaction. This research employed qualitative research design and applied discourse analysis method in analyzing the teacher’s behavior. The research participants were English teachers of SMA Islam Athirah Baruga. The data were collected by employing video recording. The results of this research revealed that (1) the kinds of approval and disapproval behavior used by EFL teachers in classroom interaction were categorized into three level namely strong, moderate and weak for approval and disapproval behavior included verbal and non-verbal behavior, those approval behaviors such as: “thank you”, “good”, “excellent”, “exactly” and “clap hands” and for disapproval behaviors were “pay attention”, “silent”, “no voice”, “pointing students” and “sstt”, (2) the most frequently use of approval and disapproval uttered by teachers was “okay”, then for disapproval was “pay attention”. Key words: Approval Behavior, Disapproval Behavior, Classroom Interaction